Nocebo as a potential confounding factor in clinical trials for Parkinson's disease treatment: a meta‐analysis. Issue 3 (12th November 2012) - Stathis, P.; Smpiliris, M.; Konitsiotis, S.; Mitsikostas, D. D.
<x xml:space="preserve">Abstract</x> Background and purpose Nocebo refers to adverse events (AEs) generated by patient's negative expectations that medical treatment will likely harm instead of heal and can be assessed in placebo‐controlled randomized controlled trials (RCTs). We examined AEs following placebo administration in RCTs for Parkinson's disease (PD). Methods After a systematic Medline search for RCTs for PD pharmacologic treatments published between 2000 and 2010, we assessed percentages of placebo‐treated patients reporting at least one AE or discontinuing due to placebo intolerance and searched for factors influencing nocebo's extent. Results Data were extracted from 41 RCTs fulfilling search criteria. Of 3544 placebo‐treated patients, 64.7% (95% CI: 53.6–74.4) reported at least one AE and 8.8% (95% CI: 6.8–11.5) discontinued placebo treatment due to intolerance. The number of AEs per 100 person‐months was 25.9 (95% CI: 16.8–39.8). Nocebo dropout rate was positively related to study population size and year of publication. Increased number of AEs per 100 person‐months was negatively correlated with the duration of treatment. AE rates, dropout rates, and AEs per 100 person‐months in placebo‐ and active drug‐treated patients were strongly correlated (r = 0.941, 0.695, and 0.824, respectively). Conclusions Our analysis indicates a significant dropout rate related to nocebo in trials for PD treatment. Adherence and efficacy may be adversely affected with additional implications for clinical practice.